DETECCIÓN DE ILEITIS NECRÓTICA CAUSADA POR Lawsonia intracellularis EN PORCINOS DE GRANJAS TECNIFICADAS DE LA ZONA DE LIMA - Calle E., Sonia (2006)
The objective of the present study was to determine the presence of Lawsonia intracellularis in Peru. A total of 197 serum samples were evaluated by the immunofluorescence test. The seroprevalence was 38.7% (73/197) and most of the affected animals were in the fattening stage. Eight percent of animals showed diarrhea and lost of body condition. Slaughtered animals showed various anatomical ileal damages. The histopathological lesions in ileon were compatible with necrotic ileitis caused by Lawsonia intracellularis. The Warthin Starry technique was used to confirm these results.